Oral health disparities among underserved populations in Nigeria - Arua, Samuel Oko; Ngwu, Chika Charity; Agbo, Emmanuel Emenike; Haggai, Silas; Ucheka, Promise Ifeanyi (Orapuh Journal, 2022)
The prevalence of oral health problems has remained a global challenge and efforts are being made to address the challenge but there is a lot of disparity in underserved rural areas. The poor and socially disadvantaged people especially those in the underserved areas lack equal opportunity to access adequate oral healthcare services and this is the major cause of the high prevalence of untreated or poorly treated oral health problems in rural communities. This review aimed to highlight the oral health disparities in underserved populations; and for the success of the review, we searched databases such as PubMed, Google Scholar, MEDLINE, Cochrane Library, and Microsoft Academic to obtain up-to-date literature. We restricted the search to articles published within the last decade but due to the scarcity of publications in most developing countries of interest such as Nigeria, we included older publications to enable us to get a comprehensive view of the disparities in these areas.  Results showed that poor and rural communities suffer a lot of oral health disparity because there are no dental care facilities available in their communities, they lack orientation about the importance of good oral health, the cost of accessing dental services is high, and there is not enough workforce to meet the overwhelming need for oral healthcare intervention. These imply that these underserved populations are deprived of the opportunity to have a healthy mouth.